2019
DOI: 10.1016/j.heliyon.2019.e01949
|View full text |Cite
|
Sign up to set email alerts
|

Subway tunnels displacement analysis due to two different communication channels construction procedures

Abstract: Due to congestion in overground space, many underground structures have been built to facilitate communications between cities. These structures constructions will induce soil displacement, cities planning rearrangement, and sometimes are near to future buildings constructions. In some cases, communication channels should be built to allow the underground junction between the building and the subway station. Numerical simulation has been carried out to study the tunnel displacement behavior during construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The surcharge loading effect, however, was disregarded in the model. Fall et al [15] reported the application case of the double-row sheet pile wall in deep foundation pits near the subway lines. The results of the numerical calculation and field measurement demonstrated that the deformation of the foundation pit of the double-row sheet pile wall is relatively small.…”
Section: State Of the Artmentioning
confidence: 99%
“…The surcharge loading effect, however, was disregarded in the model. Fall et al [15] reported the application case of the double-row sheet pile wall in deep foundation pits near the subway lines. The results of the numerical calculation and field measurement demonstrated that the deformation of the foundation pit of the double-row sheet pile wall is relatively small.…”
Section: State Of the Artmentioning
confidence: 99%
“…Taking building information modelling (BIM) as the risk identification platform, Ganbat et al [12] set up a mechanism that can identify the risks accurately and timely in the early stage of construction. With the aid of engineering software [13][14][15] simulated how excavating deep foundation pit disturbs the soil and affects the displacement of underground pipelines, and introduced additional reinforcement to the hazardous areas [16,17] regarded tunneling risk as the equivalent of excavating risk of foundation pit, designed reinforcement measures against instability and deformation, and successfully applied the measures in metro station construction.…”
Section: Introductionmentioning
confidence: 99%